The effectiveness of intravenous parecoxib sodium as an analgesic alternative to morphine in suspected acute renal colic in Emergency Department Hospital Universiti Sains Malaysia - Ismail, Azirawati (2016)
Background : Patients with renal colic usually presented to Emergency Department with severe and excruciating pain. Emergency Physicians using numerous medications to treat the problem, however none of them had been proven to relieve the pain completely. This study aimed to compare the effectiveness of IV parecoxib versus IV morphine in suspected acute renal colic in Emergency Department . Objectives : The objectives of this study were comparison between IV parecoxib sodium and morphine in Emergenency Department HUSM regarding pain score reduction among acute renal colic patient over time, mean pain score reduction by group over time and to compare the effectiveness of both analgesics (reduction by 2 pain scores) after 5 minutes of drug administration. The side effects of both drugs will be evaluated too. Methods : A randomized, single-blinded study comparing IV parecoxib 40 mg versus IV morphine at 0.10 mg/kg was conducted in adult patients who presented with features suggestive of acute renal colic and NRS of 6 or more. Periodic assessment of vital signs and NRS were taken at 0, 5, 15 and 30 minutes as well as evaluation of side effects within 30 minutes after the administration of the study drugs. The primary outcome was the reduction of NRS. The data was analyzed by repeated measures ANOVA analysis. Results : There was no significant difference in the mean NRS between patients in IV parecoxib group and morphine group over time (F(3,126)=0.229, P=0.876). Comparison of the effectiveness at 5 minutes between the groups was not significant (P=0.498). Dizziness, vomiting and nausea were experienced in 22.7%, 13.6% and4.5% of patients respectively in IV morphine group as compared to parecoxib group 4.5% experienced of nausea only. Conclusions : There was no significant difference in NRS between the groups over time, as well as in term of the effectiveness at 5 minutes. Due to lack of IV parecoxib side effect compared to morphine, IV parecoxib seemed to be valuable in the future and can be used as analgesic alternative to morphine in acute renal colic as well as extended further to treat a variety of cases presented in ED HUSM.